Quality of intrapartum care at health centers in Jabi Tehinan district, North West Ethiopia: clients' perspective - Kerebih Asrese (BMC, 2020)
Abstract Background Despite progress recently, Ethiopia remains one of the largest contributors to the global burden of maternal deaths. As facility-based childbirth and skilled-birth attendant at birth reduces maternal morbidity and mortality, the country has been implementing expansions in infrastructure during the past decades. Whether this phenomenal expansion in infrastructure and improvement in coverage of healthcare services matched with quality of maternal health service is not well investigated. This study assessed the quality of intrapartum care experienced by mothers at health centers in Jabi Tehinan district, North West Ethiopia. Method An institution-linked community-based cross-sectional study was carried out from August to September 2018 to assess the quality of intrapartum care experienced by mothers during facility deliveries. Quantitative data were collected from 378 women who had uncomplicated births at health centers within 6 months preceding the survey and interviews were held with 25 women. The quantitative data were entered into SPSS for Windows versions 23 for analyses. Qualitative data were transcribed verbatim and data were used to substantiate the quantitative data. Result The results indicated that 13% of mothers experienced good quality of intrapartum care services. About 49, 45, 31, and 25% of mothers respectively experienced good quality of human and physical resources; respect, dignity, and equity; emotional support; and cognition. Only 2% of mothers experienced good quality of services on the four dimensions and 15% did not experience good quality of services on neither of the dimensions. Mothers from rural areas and mothers who did not use ANC services for recent born children were found more likely to experience good quality of intrapartum care. Informants discussed poor quality of labor environment, lack of privacy, and poor client-provider communications at health facilities. Conclusion The results indicated that the quality of intrapartum care experienced by mothers were minimal. The findings highlighted that efforts exerted to increase infrastructure and improve maternal health service coverage did not ensure quality maternal health services. Therefore, to increase the uptake of facility births and improved maternal health outcomes, stakeholders should make the health system humane, respectful, equitable, and responsive to mothers' concerns.